2023
DOI: 10.3390/antibiotics12040785
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Cefiderocol on Multiresistant Bacterial Strains and Genomic Analysis of Two Cefiderocol Resistant Strains

Abstract: Cefiderocol is a new siderophore cephalosporin that is effective against multidrug-resistant Gram-negative bacteria, including carbapenem-resistant strains. The aim of this study was to evaluate the activity of this new antimicrobial agent against a collection of pathogens using broth microdilution assays and to analyze the possible mechanism of cefiderocol resistance in two resistant Klebsiella pneumoniae isolates. One hundred and ten isolates were tested, comprising 67 Enterobacterales, two Acinetobacter bau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Here, it was observed that cefiderocol, along with ceftazimideavibactam and meropenem-vaborbactam, are effective against severe, uncommon infections caused by microorganisms producing carbapenemases (Sadek et al 2023). In addition to this, the in vitro evaluation of cefiderocol against Enterobacterales, Acinetobacter baumannii, and Pseudomonas aeruginosa, among others, showed that this compound was able to inhibit 94% of the isolates (Padovani et al 2023), and in a surveillance study conducted with Gram-negative bacterial clinical Fig. 1 A schematic representation of the mediated iron uptake by microbial siderophores is shown.…”
Section: Siderophores Used As Antimicrobial Agentsmentioning
confidence: 91%
See 1 more Smart Citation
“…Here, it was observed that cefiderocol, along with ceftazimideavibactam and meropenem-vaborbactam, are effective against severe, uncommon infections caused by microorganisms producing carbapenemases (Sadek et al 2023). In addition to this, the in vitro evaluation of cefiderocol against Enterobacterales, Acinetobacter baumannii, and Pseudomonas aeruginosa, among others, showed that this compound was able to inhibit 94% of the isolates (Padovani et al 2023), and in a surveillance study conducted with Gram-negative bacterial clinical Fig. 1 A schematic representation of the mediated iron uptake by microbial siderophores is shown.…”
Section: Siderophores Used As Antimicrobial Agentsmentioning
confidence: 91%
“…Here, it was observed that cefiderocol, along with ceftazimide-avibactam and meropenem-vaborbactam, are effective against severe, uncommon infections caused by microorganisms producing carbapenemases (Sadek et al 2023 ). In addition to this, the in vitro evaluation of cefiderocol against Enterobacterales , Acinetobacter baumannii , and Pseudomonas aeruginosa , among others, showed that this compound was able to inhibit 94% of the isolates (Padovani et al 2023 ), and in a surveillance study conducted with Gram-negative bacterial clinical isolates from North America and Europe (2014 to 2019) showed that cefiderocol inhibits in average > 90% of Enterobacterales , > 96% of A. baumannii and > 99% of P. aeruginosa isolates non-susceptible to diverse carbapenems (Karlowsky et al 2022 ). These results are also promising in clinical trials where cefiderocol has been successfully used to treat severe infections with carbapenem-resistant Gram-negative bacteria, achieving clinical and microbiological cure of up to 84.6% of the patients 7 days after the treatment has ended (de la Fuente et al 2023 ).…”
Section: Siderophores Used As Antimicrobial Agentsmentioning
confidence: 97%
“…Five consecutive annual SIDERO-WT Studies reports a 99.9% of susceptibility to cefiderocol in a total of 7700 isolates. [54,60,74] Whole genome sequencing of P. aeruginosa non-susceptible to cefiderocol identified mutations in major iron transport pathways. The second study reports in vivo development of cefiderocol resistance among four sequential P. aeruginosa clinical isolates ST244 recovered from a single patient, without exposure to cefiderocol.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…[ 54,60,74] S. maltophilia strains evolved cefiderocol resistance through different genetic pathways, but often involved iron transport.…”
Section: Stenotrophomonas Maltophiliamentioning
confidence: 99%
See 1 more Smart Citation